The Influence of Quality Perceptions on Repurchase Intentions Of Miniso Products in Jabodetabek - yoza, yoza aresta; Dwi Lestari, Unik (ASIAN PUBLISHER, 2023)
The purpose of this study is to analyze the effect of perceived quality on repurchase intentions. This type of research is quantitative using a purposive sampling method on 135 customer respondents who buy miniso products in Jabodetabek. The method used to analyze it is the structural Equation Model (SEM-PLS) using the SmartPLS device. The findings of this study are perceived quality has a positive effect on perceived value, perceived quality has a positive effect on satisfaction, perception has a positive effect on repurchase intentions, satisfaction has a positive effect on loyalty, perceived value has no effect on loyalty, satisfaction has no effect on repurchase intentions, perceived quality has no effect on repurchase intention, perceived quality has no effect on repurchase intention and loyalty has a positive effect on repurchase intention.